PHASE TRANSFORMATIONS AND DEFECT STRUCTURE DURING MULTISTAGE QUENCHING OF TOOL CARBON STEELS (Web of Technology: Multidimensional Research Journal, 2026)
This study investigates phase transformations and defect structure formation in tool carbon steels (U7 and U11) subjected to multistage quenching. It is established that high-temperature heating prior to the first quenching leads to the formation of a coarse-grained structure and an increased dislocation density, which is inherited during subsequent heat treatment stages. It is shown that re-quenching from standard recommended temperatures results in phase recrystallization and the formation of a fine-grained structure; however, a high level of defects is retained. The influence of the first quenching temperature and inter-quench tempering on dislocation density, grain size, hardness, and carbon distribution between martensite and retained austenite is analyzed. It is found that the increase in dislocation density is governed by two main factors: inheritance of the defect structure formed during high-temperature quenching and the formation of new grains during reheating, accompanied by microdistortions in the crystal lattice. Increasing the tempering temperature leads to a gradual relaxation of internal stresses. The results obtained provide deeper insight into the mechanisms of structure formation during multistage quenching and support the optimization of heat treatment regimes for tool steels.